Peningkatan Literasi Digital melalui Pemanfaatan Teknologi Informasi di SMP Negeri 3 Sumberasih Satu Atap Probolinggo - Sudriyanto ,; Kamil Malik; Feriska Listrianti (Abhakte Jurnal Pengabdian Kepada Masyarakat, 2024)
This study aims to address the limited access to information technology at SMP Negeri 3 Sumberasih Satu Atap, Probolinggo, by implementing an information technology-based education program designed to enhance the digital literacy of students and teachers. The research employed both qualitative and quantitative methods to evaluate the effectiveness of the interventions conducted. These interventions included a series of information technology training workshops, the installation of adequate information and communication technology (ICT) infrastructure, and student leadership sessions aimed at developing leadership capabilities and organizational skills among the students. During the study, a participatory approach was adopted to ensure the active involvement of all relevant parties, including students, teachers, and school administrative staff. This not only aided in the smooth implementation of the program but also facilitated the adoption of new practices and norms in a more inclusive and technology-oriented learning process. The results of this study showed a significant improvement in digital literacy among the participants. Students and teachers became more proficient in using digital tools for teaching and learning processes. Additionally, there were positive social changes within the school environment, marked by the emergence of young leaders who initiated the use of technology for various educational activities. This research indicates that with proper support and adequate infrastructure, schools with limited access to technology can experience significant digital transformation.